2014
DOI: 10.1519/jsc.0000000000000477
|View full text |Cite
|
Sign up to set email alerts
|

Influence of New Military Athletic Footwear on the Kinetics and Kinematics of Running in Relation to Army Boots

Abstract: Musculoskeletal injuries in the lower extremities are common in military recruits. Army boots have frequently been cited as a potential mechanism behind these high injury rates. In response to this, the British Army introduced new footwear models, the PT-03 (cross-trainer) and PT1000 (running shoes), which are issued to each new recruit in an attempt to reduce the incidence of these injuries. The aim of the current investigation was to examine the kinetics and kinematic of the PT-03 and PT1000 footwear in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
4
15
0
Order By: Relevance
“…and are comparable with peak vGRF and vertical RFD apparent in high level plyometric drills[29]; demonstrating that foot-drill represents a substantial mechanical load placed on the MSK structures of the lower-extremities. The Halt foot-drill exhibited the greatest mean peak vGRF (5.3 ± 0.6) and vertical RFD (313.9 ± 30.2) when compared with the remaining foot-drills, with SaE and SaA exhibiting vGRF and vertical RFD in excess of 4.9BW and 278.1BW/s, respectively (figure 3).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…and are comparable with peak vGRF and vertical RFD apparent in high level plyometric drills[29]; demonstrating that foot-drill represents a substantial mechanical load placed on the MSK structures of the lower-extremities. The Halt foot-drill exhibited the greatest mean peak vGRF (5.3 ± 0.6) and vertical RFD (313.9 ± 30.2) when compared with the remaining foot-drills, with SaE and SaA exhibiting vGRF and vertical RFD in excess of 4.9BW and 278.1BW/s, respectively (figure 3).…”
supporting
confidence: 59%
“…This study has reported foot-drill mean peak vGRF and vertical RFD data similar to those reported in previous foot-drill research [5,9] One limitation of the current investigation is the all-male sample. Previous biomechanical studies have demonstrated that recreationally active females exhibit distinct loading mechanics and lower-limb kinematics when compared with their male counterparts [5,29]. Thus, it is unlikely that these results can be generalizable to a recreationally active female population.…”
Section: Discussionmentioning
confidence: 82%
“…The CB is issued to entry-level recruits on induction to BMT, and worn with uniforms on a daily basis, and by military units on parade in full dress uniform 7 . The AB [or similar] is commonly worn by British military personnel in dress uniform or during ceremonial and/or drill duties 17 fracture of the foot and/or shank 4,27 . Furthermore, these specific vGRF and temporal parameters have been utilised to indirectly assess the shock absorbing functionality of specific footwear, during a variety of lower-limb tasks 12,13,27 .…”
Section: Introductionmentioning
confidence: 99%
“…The AB [or similar] is commonly worn by British military personnel in dress uniform or during ceremonial and/or drill duties 17 fracture of the foot and/or shank 4,27 . Furthermore, these specific vGRF and temporal parameters have been utilised to indirectly assess the shock absorbing functionality of specific footwear, during a variety of lower-limb tasks 12,13,27 . For example, previous footwear research has demonstrated that the CB, when compared with other military and commercially available footwear, produces significantly greater impact loading forces when running and marching at velocities of 4m-s 1 and 1.5ms 1 , respectively 12,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Among other factors, military boots differ from running shoes in design (shaft), weight (heavier), and sole flexibility (stiffer) . In studies comparing running in shoes versus running in military boots at 10 km/h on a treadmill, conflicting results were presented; one research group found no significant differences in stride length, cadence, and maximal vertical ground reaction forces, but in one other study running at 14.4 km/h in army boots was associated with significantly greater loading impact compared with cross‐trainer and running type shoes . The goal of conservative treatment of ERLP in military patients is to help them return to military duties, including running in boots, without re‐injury.…”
Section: Introductionmentioning
confidence: 99%